WORKING WITH DIFFERENT PROFICIENCY LEVELS IN THE ENGLISH EFL CLASSROOM: OUT-OF-CLASS ACTIVITIES - Xo‘jayeva, Saodatxon Mo‘minjon qizi; Jalolova, M.B (Educational Research in Universal Sciences, 2024)
This article provides an overview of the study’s focus on working with different proficiency levels in the English as a Foreign Language (EFL) classroom, specifically exploring out-of-class activities. The study aims to examine the impact of out-of-class activities on the language development of students with varying proficiency levels. It also seeks to identify effective strategies for incorporating out-of-class activities to address the diverse needs of learners. The findings are expected to contribute to the enhancement of EFL teaching and learning, providing valuable insights for educators, curriculum developers, and policy makers.